Environmental Structure and Theories of Strategic Choice - Whittington, R (1988)
This article argues that the prevailing dichotomization of organizational studies into voluntarist and deterministic orientations is too simple, and that this simplicity has dangerous consequences for accounts of strategic choice. Determinism has been equated exclusively with the operation of environmental constraint, with the implication that the agency necessary for strategic choice can be secured simply by the removal of this constraint. This focus on external constraint has obscured the continuing influence of ‘action determinist’ positions, in which action is determined by mechanisms internal to the actor him/herself. This article argues that many recent theorists of strategic choice have relied too much on the interpretive voluntarist dissolution of environmental structure and neglected to safeguard themselves from the action determinism latent in the Carnegie tradition. the article proposes an alternative Realist account that, by contrast with interpretive voluntarism, incorporates environmental structure as an essential precondition to actors’ internal and external capacities for strategic choice.